EMERGENCY CONTRACEPTION: KNOWLEDGE, ATTITUDE AND PRACTICES AMONG DOCTORS OF A TERTIARY CARE HOSPITAL - Alam, Kinza; Snover, Ayesha; Sultana, Nadra; Munir, Tahir Ahmad; Shah, Syed Shoaib (Journal of Ayub Medical College Abbottabad, 2013)
Background: In Pakistan maternal mortality rate (MMR) is very high and more than one in five women die from pregnancy related causes; solution to this is to have low fertility rate. The emergency contraceptives (ECs) can be used to prevent unwanted pregnancies. The aim of this study was to assess the knowledge, attitude and practice about ECs among doctors. Methods: Institution-based cross-sectional descriptive study on knowledge, attitude and practice of ECs was conducted at Rawal Hospital from Feb to May, 2012. Data was collected using structured questionnaire and analysed using SPSS-16. Results: Fifty-seven percent of the respondents were >30 years of age, 94% were Muslim, 81% were married and 51% were women. Ninety-seven percent had heard of ECs before, only 17% knew Intra-uterine contraceptive device (IUCD) a method of EC. Sixty-one percent responded that IUCD should be removed if patient gets pregnant (p=0.007) and according to 31% ECs were not abortifacient (p=0.045). Regarding attitude, 55.5% of the participants supported its use (p=0.027) and agreed to its easy accessibility (p=0.004). Thirty-eight percent responded an increased dose of birth control pills as a form of EC (p=0.008), while 40% did not agree that ECs are effective when taken before intercourse (p=0.011). Conclusion: Knowledge and practice of ECs is very low among doctors but a positive attitude is there. Evidence-based knowledge to family physicians regarding emergency contraception is strongly recommended to reduce the chances of MMR. Keywords: Attitude, Emergency Contraception, Knowledge, Practice, Maternal Mortality Rate